CASK Silence Overcomes Sorafenib Resistance of Hepatocellular Carcinoma Through Activating Apoptosis and Autophagic Cell Death - Ding, Bisha; Bao, Chang; Jin, Luqi; Xu, Liang; Fan, Weimin; Lou, Weiyang (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) patients usually fail to be treated because of drug resistance, including sorafenib. In this study, the effects of CASK in HCC were investigated using gain- or loss-of-function strategies by performing cell counting kit-8 assay, colony formation assay, flow cytometry, transmission electron microscopy, immunofluorescent confocal laser microscopy, tumor xenograft experiment and immunohistochemistry staining. The current results suggested that CASK expression was positively associated with sorafenib resistance and poor prognosis of HCC. Moreover, inhibition of CASK increased the role of sorafenib partially by promoting apoptosis and autophagy, while CASK overexpression presented the opposite effects. Besides, when treatment with sorafenib, inhibition of apoptosis using the pan-caspase inhibitor Z-VAD-FMK and inhibition of autophagy using autophagy inhibitor 3-Methyladenine (3-MA) or small interfering RNA (siRNA) of LC3B all significantly reversed CASK knockout-induced effects, suggesting that both apoptosis and autophagy were involved in CASK-mediated above functions and autophagy played a pro-death role in this research. Intriguingly, similar results were observed in vivo. In molecular level, CASK knockout activated the c-Jun N-terminal kinase (JNK) pathway, and treatment with JNK inhibitor SP600125 or transiently transfected with siRNA targeting JNK significantly attenuated CASK knockout-mediated autophagic cell death. Collectively, all these results together indicated that CASK might be a promising biomarker and a potential therapeutic target for HCC patients.